Design optimization of passenger SUV's crash box and bumper beam by using finite element method - Ahmad Yunus, Nasution; Mohd Ruzaimi, Mat Rejab; Ma, Quanjin; Firmansyah, Mohamad Ardy (IOP Publishing Ltd., 2021)
The accident cases with front crash type occupy the largest data statistics with 7,372 cases. Theoretically, the accident cases which involve passenger cars, kinetic energy is absorbed by the complex system. Some components which are included in the system are crash box and bumper beam. The main purpose of this research is to obtain the absorption of kinetic energy when the accident happened, types of deformation, and optimization in the existing designs of crash box and bumper beam from vehicle unit. Finite element method combines with analytical value are used in the simulation. Whereas, the software used in solid modelling is SolidWork and the numerical analysis used in this research is Abaqus / Explicit. The average reaction force through simulation is obtained by averaging the results of curve plotting, while the average reaction force is obtained through formula analysis by taking material property and dimension data and then inputting it in the calculation. From the simulation, energy absorbed is 9,912 Joule from the whole original structure. The energy absorbed is less than the crash box work which is 14,066 Joule within an error value of 22 %. This is caused by the bending moment which is emerged by bumper beam. Then, optimization is done by increasing lateral lengths of bumper beam with 20 mm, 15 mm and 10 mm, therefore energy absorption increased with 20,362 Joule, 31,886 Joule and 16,348 Joule, respectively.